Macroalgae As a Source of Food And Health For Coastal Communities in Moluccas Province - Tuaputty, Hasan; Papilaya, Pamela Mercy; Tuapattinaya, Prelly; Parry, Cornelia; Alimudi, Saiful (BIOEDUPAT: Pattimura Journal of Biology and Learning, 2024)
These various types of macroalgae have an important role in the lives of coastal communities as a source of nutritious food and also have ecological and biological functions in maintaining the stability of marine ecosystems and as a place to live and protect other biota. This group of macroalgae has economic potential, namely as food, raw materials in industry and health. To find out macroalgae as a source of food and health, a study was carried out using a collaborative experimental research approach in the F-MIPA Laboratory at Pattimura University and field surveys in various districts of Moluccas Province.Types of macroalgae consumed by people in Maluku Province include: Eucheuma conttonii, Gracilaria salicornia, Caulerpa lentillifera, Kappaphycus alvarezii, Gracilaria arcuate species. Of these 5 types of macroalgae, 4 species are red macroalgae class Rhodophycea and 1 species is green macroalgae class Chrorophycea. The results of proximate analysis show that macroalgae are consumed by the public. The highest carbohydrate content in the macrolaga Gracilaria arcuata was 2.1370%, the highest proteins content in the macroalgae Eucheuma conttonii was 0.9161%, the fat content in the macrogaze was highest in the Kappaphycus alvarezii type at 0.4053%, the highest ash content in the macroalgae was in the Eucheuma conttonii type at 5.8155%. The highest water content contained in various types of macroalgae in the macroalgae Caulerpa lentillifera was 93.5485%. There is a linear correlation between the knowledge of coastal communities in several districts of Maluku Province who consume macroalgae as a source of food and health, and the attitude of coastal communities towards cooking menus made from macroalgae. This is proven by the analysis results showing an R value of 2 = 0.779, which means there is a significant correlation between knowledge. and public attitudes about macroalgae as a source of food and health. The existence of this significant relationship is due to the influence of knowledge of 77.9% on the attitudes of people who consume macrolaga, and only 22.1% is influenced by other factors. The results of the analysis show that there is an influence of knowledge on people's attitudes about macrolags as a source of food and health. According to the results of the analysis, it shows a value of df = 44-43 = 1 with a value of F = 221,690 with a significance level of 000, <p 0.05, this means that there is The significant influence between people's knowledge and attitudes towards the food menu comes from various types of macroalgae.